ANAESTHESIOLOGY AND INTENSIVE CAREThe efficacy of thoracic epidural and paravertebral blocks for post-thoracotomy pain management - Sagiroglu, Gonul; Baysal, Ayse; Copuroglu, Elif; Karamustafaoglu, Yekta Altemur; Sagiroglu, Tamer; Yuksel, Volkan; Huseyin, Serhat (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Introduction : The definition of pain focuses mainly on tissue damage and provides information regarding pathophysiological changes in the human being [1]. Patients experience pain as a response to this tissue damage after surgery and the pain intensity after thoracotomies is known to be severe [2]. Aim of the study : Our goal was to investigate the efficacy and adverse effects of thoracic epidural and paravertebral blocks for post-thoracotomy pain management. Material and methods : In a prospective, randomized double blinded study, patients were divided into thoracic epidural (EPI group, n = 30) and paravertebral (PVB group, n = 30) groups. A bolus dose of 10 ml of 0.25% bupivacaine was followed by a continuous infusion of 0.1 ml kg –1 h –1 for a total of 24 hours. A visual analog scale (VAS) was used to evaluate pain at rest (VAS-R) and after coughing (VAS-C) at baseline (after extubation), 2, 4, 12 and 24 hours after surgery. The duration of catheter insertion, morphine consumption, complications and side effects were collected. Results: In comparison of EPI and PVB groups, VAS-R and VAS-C scores were similar at baseline and at 2, 4, 12 and 24 hours after surgery (p > 0.05). The incidence of hypotension was higher and the duration of catheter insertion was longer in the EPI group in comparison to the PVB group (p = 0.038, p < 0.0001, respectively). Conclusions : For post-thoracotomy pain, both thoracic epidural analgesia and paravertebral block techniques provide sufficient pain relief. As paravertebral block is an easier and quicker technique with lower incidence of hypotension, it should be considered as a good alternative to thoracic epidural technique to establish postoperative analgesia.